Avaliação do potencial antioxidante e atividade vasorrelaxante de Cinnamomum sp. - Moreno, Emily Kussmaul Gonçalves (2023)
The great interest in the study of antioxidants is mainly the prevention of physiological damage caused by oxidative processes. Cinnamon (Cinnamomum sp.), is a spice used worldwide in cooking and has gained prominence for its pharmacological properties, such as anti-inflamatory, antibacterial, antifungal, cardiovascular, among others. Given the importance of determining the antioxidant capacity in relation to therapeutic methods, this study aims to evaluate the antioxidant profile of commercial cinnamon samples by spectrophotometric, electrochemical and vasorelaxant methods. The spectrophotometric methods performed were 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinobis (3- ethylbenzothiazoline-6-sulfonic acid) (ABTS) and Folin-Ciocalteu. For the electrochemical experiments, a three-electrode system was used, consisting of carbon paste electrode, platinum wire, and Ag/AgCl/KClsat, representing the working, auxiliary, and reference electrodes, respectively. The electroanalytical methods used were differential pulse, square wave, and cyclic voltammetries. Vascular reactivity was evaluated in aortic artery rings from male Wistar rats, using arteries with intact vascular endothelium and without endothelium. The endothelial nitric oxide synthase (eNOS) pathway and the inhibitor N-nitro-L-arginine-methylester (L-NAME) were used in this analysis. The correlation between the electrochemical approach and total phenols by the ABTS, DPPH, and Folin- Ciocalceu methods were 0.63, 0.70, and 0.73, respectively, with 1 being an ideal correlation. The correlation between spectrophotometric methods was 0.83. For the electrochemical results, a similar profile was observed, with anodic peak a.c Epa1= 0.1 V, indicative of polyphenolic compounds with high antioxidant power. In addition, a biosensor on a carbon paste electrode was applied to the selected extracts using laccase enzyme, obtained by the fungus Marasmiellus sp. and a signal improvement of up to 4 times in the antioxidant profile was observed when compared to the electrode without modification. The samples were analyzed by mass spectrometer, and the main chemical markers found were coumarin, cinnamaldehyde, and eugenol. Pharmacological assays showed that these samples also promoted a significant vasorelaxant effect associated to the antioxidant potential. Thus, cinnamon showed a high antioxidant capacity, in agreement with the results obtained in other studies, emphasizing its importance as a functional food.